2005
DOI: 10.1177/016235320502900103
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Attitudes toward Academic Acceleration and Accelerated Students in the Netherlands

Abstract: In a survey study, we investigated teacher attitudes toward acceleration and accelerated students in the Netherlands. Teachers ( N = 334) from 31 secondary schools gave their opinion about gifted education and acceleration, and evaluated statements about accelerated students. Most teachers considered a special approach for gifted students advisable and acceleration a useful intervention. Teachers' opinions about accelerated students' social competence, school motivation and achievement, emotional problems, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 13 publications
6
47
1
1
Order By: Relevance
“…As such, teachers' acceptance of an educational policy might depend heavily on their beliefs about it but also on their knowledge (Drake, 2006). Often, teachers' negatively tinged attitudes toward giftedness and gifted education can primarily be attributed to a lack of knowledge and understanding (Clark, 2002;Gross, 1994;Vock et al, 2007), and there is evidence that informing teachers about grade skipping might improve their acceptance of it (Hoogeveen et al, 2005). In addition, as Vock et al (2007) argue, increases in the frequency of grade skipping that have been reported in Germany might in fact have led to increases in awareness and in turn to more favorable attitudes.…”
Section: Teachers' Roles In Implementing Grade Skipping and Their Accmentioning
confidence: 99%
See 4 more Smart Citations
“…As such, teachers' acceptance of an educational policy might depend heavily on their beliefs about it but also on their knowledge (Drake, 2006). Often, teachers' negatively tinged attitudes toward giftedness and gifted education can primarily be attributed to a lack of knowledge and understanding (Clark, 2002;Gross, 1994;Vock et al, 2007), and there is evidence that informing teachers about grade skipping might improve their acceptance of it (Hoogeveen et al, 2005). In addition, as Vock et al (2007) argue, increases in the frequency of grade skipping that have been reported in Germany might in fact have led to increases in awareness and in turn to more favorable attitudes.…”
Section: Teachers' Roles In Implementing Grade Skipping and Their Accmentioning
confidence: 99%
“…Thus, the amount of experience that teachers have with students who have skipped a grade may contribute to teachers' acceptance, too. Accordingly, Hoogeveen et al (2005) showed that teachers' attitudes toward grade skipping were associated with the extent to which they had experience in dealing with accelerated students. Therefore, in the current study, we took into account teachers' perceptions of their knowledge and their experience with students who had skipped a grade when exploring the role that teachers' beliefs about students' development after grade skipping play in teachers' acceptance.…”
Section: Teachers' Roles In Implementing Grade Skipping and Their Accmentioning
confidence: 99%
See 3 more Smart Citations